Nephtyidae (Annelida: Polychaeta) from the Sea of Marmara and Black Sea, with descriptions of two new species - Kuş, Sevgi; Kurt, Güley; Çinar, Melih Ertan (Zootaxa, 2021)
The present paper deals with the diversity of nephtyid polychaetes (Nephtyidae) from the Sea of Marmara and the Black Sea. Three species belonging to two genera (Micronephthys and Nephtys) were found in the Black Sea (coast of Turkey) and six species belonging to three genera (Inermonephtys, Micronephthys and Nephtys) were found in the Sea of Marmara. The material includes two species new to science, Inermonephtys turcica n. sp. and Nephtys sinopensis n. sp., and a species record (Nephtys kersivalensis McIntosh, 1908) new to the Sea of Marmara’s marine fauna. Nephtys sinopensis n. sp. is mainly characterized by having 1–4 geniculate chaetae in the postacicular position of the parapodia; digitiform antennae, palps, and ventral cirri at chaetiger 1 with swollen tips; small and cirriform branchiae present from chaetiger 4 to the end of the body; poorly developed parapodial prechaetal lamellae in median and posterior chaetigers and long ventral cirri along the body. Inermonephtys turcica n. sp. is mainly characterized by having cushion-like palps with digitiform tips; well developed neuropodial postchaetal lamellae; barred chaetae in preacicular position of the anterior and median parapodia; and branchiae first appearing between chaetiger 3 and 13 (depending on body size).